NEW SYNTHESIS OF NH$_2$/NH$_2$ CAPPED POLYANILINE TETRAMERS 4,4'-DI(p-AMINOANILINO)-DIPHENYLAMINE (Proceedings of the YSU B: Chemical and Biological Sciences, 2013)
New method of synthesizing NH2/NH2 capped polyaniline tetramer – 4,4'-di(p-aminoanilino)-diphenylene, by oxidative condensation of 4-aminoacetanilide with N-acetyldiphenylamine and subsequent hydrolysis of the obtained 4,4'-di(p-acetylamino)-N-acetyldiphenylamine is discussed.
Keywords: polyaniline; emeraldine; tetraaniline; oxidative condensation; oligoaniline